Association between insulin resistance-related lipid indices and arthritis: a U. S. cross-sectional study - Wu, Ao; Teng, Haodong; Wang, Xiaoxia; Shi, Ketao; Gao, Zhi; Xu, Honghao; Yue, Liang (Frontiers in Nutrition, 2025)
ObjectivesArthritis is a degenerative disease that causes a huge social burden. Lipid-related molecules participate in the inflammatory response process of arthritis and are closely related to the pathological process of arthritis. Lipid-related indicators are easily available and have great potential in predicting arthritis. This study used cross-sectional data to explore lipid-related indicators and arthritis risk.Methods18,683 participants were involved in this study, selected from the NHANES database covering the period from 2001 to 2018. The study utilized multivariate regression models to examine the association between various lipid-related parameters (including the TyG index, TyG-WC index, TyG-WHtR index, TyG-BMI index, HOMA-IR index, VAI index, and LAP index) and arthritis.ResultsAfter taking into account and appropriately addressing potential confounding variables and factors, all seven lipid-related indicators were positively associated with arthritis risk, and there was a significant difference in the highest quartile of seven lipid-related indicators compared with the lowest quartile (P < 0.001). Among them, the area under the ROC curve (AUC) of TyG-WC, TyG-WHtR, TyG-BMI, and LAP was >0.6, indicating they had modest accuracy in predicting arthritis. Logistic regression analysis showed that the best Cut-off values for predicting arthritis for these indicators were as follows: TyG: 8.45 [Odds ratio (95% Cl) = 1.77 (1.62, 1.94)]; TyG-WC: 850.39 [Odds ratio (95% Cl) = 1.36 (1.24, 1.49)]; TyG-WHtR: 4.97 [Odds ratio (95% Cl) = 2.39 (2.17, 2.63)]; TyG-BMI: 255.24 [Odds ratio (95% Cl) = 1.87 (1.71, 2.05)]; HOMA-IR: 2.79 [Odds ratio (95% Cl) = 1.51 (1.39, 1.65)]; VAI: 1.35 [Odds ratio (95% Cl) = 1.60 (1.47, 1.75)]; LAP: 33.46 [Odds ratio (95% Cl) = 1.20 (1.09, 1.31)], both P-values are < 0.001.ConclusionsThe results showed that seven lipid-related markers were positively associated with arthritis risk. Enhancing the management of glucose, lipids, and insulin sensitivity may significantly reduce the risk of arthritis.